2010
DOI: 10.1074/mcp.m110.000281
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteome Analysis of Pluripotent Cells by iTRAQ Mass Tagging Reveals Post-transcriptional Regulation of Proteins Required for ES Cell Self-renewal

Abstract: Embryonic stem cells and embryonal carcinoma cells share two key characteristics: pluripotency (the ability to differentiate into endoderm, ectoderm, and mesoderm) and self-renewal (the ability to grow without change in an untransformed, euploid state). Much has been done to identify and characterize transcription factors that are necessary or sufficient to maintain these characteristics. Oct-4 and Nanog are necessary to maintain pluripotency; they are down-regulated at the mRNA level by differentiation. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 115 publications
3
45
0
Order By: Relevance
“…Our studies failed to show fatty acid metabolism, pyruvate metabolism and TCA cycle that have been shown to be up-regulated in previous studies (18,19). Our experience is consistent with the findings from O'Brien et al (31) that the t test was not an adequate statistical measure of the reproducibility of protein changes using iTRAQ. The reason might be that isobaric tags FIG.…”
Section: Proteomic Profiling Of Hfd/nd Mice Liver Mitochondria-supporting
confidence: 81%
“…Our studies failed to show fatty acid metabolism, pyruvate metabolism and TCA cycle that have been shown to be up-regulated in previous studies (18,19). Our experience is consistent with the findings from O'Brien et al (31) that the t test was not an adequate statistical measure of the reproducibility of protein changes using iTRAQ. The reason might be that isobaric tags FIG.…”
Section: Proteomic Profiling Of Hfd/nd Mice Liver Mitochondria-supporting
confidence: 81%
“…5C). This is likely to be associated with the differentiation of RACGAP1 depleted cells as suggested by O'Brien and colleagues (22).…”
Section: Human Hcc Cells Expressing High Levels Of Racgap1 Correlatedmentioning
confidence: 81%
“…We think a reason for the difference could be that the IHC score was calculated by evaluation of whole tumor, while the tissue samples for the evaluation of mRNA level were obtained from part of the tumor. O 0 Brien et al [25] demonstrated that RacGAP1 was required for differentiation of embryos and hematopoietic stem cells and concluded that RACGAP1 was post-transcriptionally regulated during blastocyte development to enable embryonic stem cell self-renewal. These mechanisms may explain the apparent differences of RacGAP1 expression determined by immunohistochemical and transcriptional analyses.…”
Section: Discussionmentioning
confidence: 99%